Pengaruh Pertumbuhan Ekonomi dan Inflasi terhadap Jumlah Penduduk Miskin di Provinsi Jambi - Halim, Abd; Mayesti, Indria; Mukti, Mukti; Rosita, Ratih (Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of economic growth and inflation on the number of poor people in Jambi Province. The research method used is secondary data analysis with descriptive analysis methods. The results of this study conclude that simultaneously there is a significant influence between economic growth and inflation on the number of poor people in Jambi Province during the period 2010-2023. While partially only the inflation factor does not have a significant effect on the number of poor people in Jambi Province.